The mystery of the missing necklace - Blyton, Enid. (b, 2013)
There is a gang of thieves using Peterswood as their headquarters! Luckily, Fatty's disguises are better than ever - no one recognises him as a balloon seller or the old man in the village. He is just the person to get the Five Find-Outers to the bottom of this mystery ... -- back cover.
Keywords: Five Find-Outers (Fictitious characters) -- Juvenile fiction; Detective and mystery stories; Five Find-Outers (Fictitious characters)